A descriptive e-learning environment for mathematics - Semião, Paulo (2014)
This article is focused in the creation of descriptive processes for subjects of mathematics in an elearning environment. The main idea is for some chosen mathematical contents try to implement processes that go beyond the binomial question-answer. The system pretends to give step-by-step solutions of questions and is intended to work with any kind of mathematics. We had tried to drawn up explanations of questions as much detailed as possible, so that each learner can progress without skilled help. Our experience tells us that the combination of lectures and session problems turn out to be much more productive and successful.